An Equation for Every Occasion : Fifty-Two Formulas and Why They Matter - Henshaw, John M. (Book collections on Project MUSE., 2014)
"In An Equation for Every Occasion, John M. Henshaw tells fifty-two entertaining stories, each inspired by a different mathematical equation. His succinct, easy-to-read narratives come from the spheres of sports, business, history, the arts, science, and technology. Anecdotes about famous equations ... appear alongside tales of not-so-famous -- but equally fascinating -- equations, such as the one that's used to determine the SPF number on a bottle of sunscreen. Drawn from the breadth of human endeavor, Henshaw's stories demonstrate the power and utility of math. He entertains us by exploring the ways that equations can be used to explain, among other things, Ponzi schemes, the placebo effect, 'dog years', IQ, the wave mechanics of tsunamis, the troubled modern beekeeping industry, and the Challenger disaster. Smartly conceived and fast paced, his book offers something for anyone curious about math and its impacts. Yet readers will find themselves learning more than just math; they'll learn about the workings of the universe. Once immersed in this book, you'll find yourself thirsting for the next equation in this original page-turner."--Jacket.